2003
DOI: 10.1152/ajpregu.00501.2002
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical responses to ACTH in neonatal rats: effect of hypoxia from birth on corticosterone, StAR, and PBR

Abstract: The adrenocortical response to hypoxia may be a critical component of the adaptation to this common neonatal stress. Little is known about adrenal function in vivo in hypoxic neonates. The purpose of this study was to evaluate adrenocortical responses to ACTH in suckling rat pups exposed to hypoxia from birth to 5-7 days of age compared with normoxic controls. We also evaluated potential cellular controllers of steroidogenic function in situ. In 7-day-old pups at 0800, hypoxia from birth resulted in increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 42 publications
5
41
1
Order By: Relevance
“…An oxidized metabolite of 18:2 n-6 has been shown to stimulate basal aldosterone production in ZG cells (11,12), as well as augment basal and ACTH-stimulated corticosterone production in ZF/R cells (3,12). StAR and PBR proteins are significantly increased in the hypoxic adrenal (29), and the involvement of lipids in this process seems quite plausible given these previous findings.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…An oxidized metabolite of 18:2 n-6 has been shown to stimulate basal aldosterone production in ZG cells (11,12), as well as augment basal and ACTH-stimulated corticosterone production in ZF/R cells (3,12). StAR and PBR proteins are significantly increased in the hypoxic adrenal (29), and the involvement of lipids in this process seems quite plausible given these previous findings.…”
Section: Discussionmentioning
confidence: 79%
“…These increases occur without an increase in plasma ACTH. Furthermore, the corticosterone response to exogenous ACTH is augmented in hypoxic pups (29). None of these changes could be explained by increased expression of genes encoding the steroidogenic enzymes, or by changes in the expression of the hypoxia-inducible transcription factor-1␣ (29,30).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Timed pregnant, Sprague-Dawley rats (Harlan, Indianapolis, IN, USA, nZ24) at 14 days gestation were obtained and maintained on a standard diet and water available ad libitum (0600-1800 h lights on). Immediately after parturition (days 21-22), dams and their pups were continuously exposed to either normoxia (21% O 2 ) or hypoxia (12% O 2 ) in an environmental chamber, as described in detail previously (Thomas & Marshall 1995, Raff et al 2000, 2003a. The experimental design is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding the mechanisms by which the resulting increase in glucocorticoid secretion occurs, as well as the physiological impact of this increase in glucocorticoids, will aid in devising strategies to mitigate the short-and long-term effects of neonatal hypoxia. We have previously demonstrated that the neonatal rat exposed to hypoxia from birth has increased plasma corticosterone that is driven by sympathetic input to the adrenal cortex rather than by corticotropin (ACTH; Raff et al 2003aRaff et al , 2004. It is possible that this ACTH-independent increase in corticosterone in the neonate exposed to chronic hypoxia from birth is a mechanism to increase circulating glucocorticoids by bypassing the stress-hyporesponsive hypothalamus and/or pituitary.…”
Section: Introductionmentioning
confidence: 99%